Preparation method of wood vinegar substitute
Through the hydrothermal reaction method combined with hydrochloric acid pretreatment and oxidant, the content of organic acid in wood vinegar liquid is improved, and the problems of high energy consumption and low organic acid content of traditional pyrolysis methods are solved, thereby achieving efficient and low energy consumption of wood vinegar liquid replacement.
Patent Information
- Application Number
- CN202411845841.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-07
AI Technical Summary
The traditional pyrolysis method produces wood vinegar liquid with high energy consumption, complex operation and large product losses. The organic acid content in wood vinegar liquid produced by hydrothermal oxidation is relatively low, only 20.89-37.91%.
The straw powder is pretreated with hydrochloric acid to reduce the overall crystallinity of the straw powder, and combined with the use of oxidants, selectively reduce the decomposition temperature of lignin. Through hydrothermal reaction and repeated freeze-thawing, a wood vinegar liquid substitute with a high acid content is prepared.
The decomposition of straw powder at a lower temperature is achieved, the content of organic acids in wood vinegar liquid is increased, energy consumption and operation complexity is reduced, and product losses are avoided.
Smart Images

Figure CN119570515A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomass products, and in particular relates to a preparation method of a wood vinegar substitute. Background Art
[0002] Wood vinegar is a byproduct of the pyrolysis of wood biomass to produce biochar. It has shown many application potentials in the agricultural field, including improving saline-alkali land, as an antibacterial agent and preservative, and as a food additive. The traditional method of using biomass to prepare wood vinegar is pyrolysis, which is obtained by pyrolysis of wood cellulose and then condensation of gaseous products. For example, the existing patent CN116831142A discloses a corn-sorghum straw wood vinegar and its preparation method and application. The patent first mixes corn straw and sorghum straw, crushes and dries them, and after preheating and cracking, heats to 300-600℃ for solid decomposition to obtain crude wood vinegar; then the crude wood vinegar is repeatedly frozen and thawed and stored for 6 months, and then filtered and distilled to retain the light components and remove the heavy components. However, the traditional pyrolysis method has the problems of high energy consumption, complex operation and large product loss.
[0003] In view of the problems existing in the above-mentioned traditional pyrolysis method for preparing wood vinegar, the prior art proposes a hydrothermal oxidation method for preparing wood vinegar. For example, patent CN106753501A discloses a method for directly preparing wood vinegar from hydrothermal biomass, wherein the biomass raw material is first crushed into particles and mixed with deionized water, and then poured into a reactor, and a weak oxidant is injected into the reactor under an inert atmosphere, and then the temperature is raised to 60-360°C and kept constant for 1-120 minutes; after the reaction is completed, the reactor is cooled to room temperature, and the product in the reactor is separated to obtain wood vinegar. However, the organic acid content in the wood vinegar prepared by this patent is only 20.89-37.91%. Therefore, how to further increase the organic acid content in wood vinegar has become a technical problem that needs to be solved in this field. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a preparation method of a wood vinegar substitute.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a wood vinegar substitute, comprising the following steps:
[0007] The straw powder is pretreated with hydrochloric acid to obtain pretreated straw powder; the pretreated straw powder, an oxidant aqueous solution and water are mixed and then subjected to a hydrothermal reaction, the solid and liquid phases are separated, and the obtained liquid phase is repeatedly frozen and thawed to obtain the wood vinegar substitute.
[0008] Technical principle: By pretreating the straw powder with hydrochloric acid, the overall crystallinity of the straw powder is reduced, and the content of lignin, cellulose, and hemicellulose in the original straw is changed, so that the straw powder can be decomposed into target substances such as organic acids at a lower temperature. Combined with the use of oxidants, the decomposition temperature of lignin is selectively reduced, and finally the decomposition of straw powder at a lower temperature is achieved, and a wood vinegar substitute with a higher acid content is obtained.
[0009] The process flow chart of the preparation method of the wood vinegar substitute provided by the present invention is shown in Figure 1 .
[0010] Preferably, the solid-liquid ratio of the straw powder and hydrochloric acid is 1:10.
[0011] Beneficial effect: The amount of hydrochloric acid used within the above range can effectively reduce the overall crystallinity of the straw powder.
[0012] Preferably, the straw powder includes cotton straw powder.
[0013] Beneficial effects: Cotton straw powder contains a large amount of lignin, cellulose and hemicellulose, which can provide more sources of wood vinegar.
[0014] Further preferably, the method for preparing the straw powder is: crushing the straw and then passing it through a 60-mesh sieve.
[0015] Preferably, the concentration of the hydrochloric acid is 2 wt %.
[0016] Beneficial effects: Using hydrochloric acid with a concentration within the above range to treat straw powder effectively changes the content of lignin, cellulose, and hemicellulose in the original straw, so that the straw powder can be decomposed into target substances such as organic acids at a lower temperature. Excessive hydrochloric acid concentration will lose some hemicellulose and reduce the source of wood vinegar.
[0017] Preferably, the pretreatment temperature is 30°C and the time is 3 hours.
[0018] Beneficial effects: The pretreatment temperature and time are controlled within the above ranges, thereby ensuring the pretreatment effect of hydrochloric acid on the straw powder.
[0019] Further preferably, the pretreatment is carried out under stirring; the stirring rate is 800r / min.
[0020] Further preferably, the pretreatment further includes filtering, washing and drying steps; the washing agent is deionized water; the drying temperature is 80° C. and the drying time is 24 hours.
[0021] Preferably, the dosage ratio of the pretreated straw powder, the oxidant aqueous solution and water is 2g:5mL:15mL.
[0022] Beneficial effects: When the amount of the oxidant aqueous solution is within the above range, the decomposition temperature of lignin can be effectively reduced and the content of target substances such as organic acids in the product can be increased.
[0023] Preferably, the mass concentration of the oxidant aqueous solution is 30%.
[0024] Preferably, the oxidant in the aqueous oxidant solution comprises hydrogen peroxide.
[0025] Preferably, the temperature of the hydrothermal reaction is 180° C., the time is 90 min, and the atmosphere is nitrogen.
[0026] Beneficial effects: Controlling the temperature and time of the hydrothermal reaction within the above range is beneficial to increasing the content of target substances such as organic acids in the product.
[0027] Preferably, the repeated freezing and thawing is: repeated freezing and thawing 10 times in liquid nitrogen and at room temperature.
[0028] Compared with the prior art, the present invention has the following advantages and technical effects:
[0029] The present invention pre-treats straw powder with hydrochloric acid to reduce the overall crystallinity of the straw powder, and changes the contents of lignin, cellulose and hemicellulose in the original straw, so that the straw powder can be decomposed into target substances such as organic acids at a lower temperature. Combined with the use of an oxidant, the decomposition temperature of lignin is selectively reduced, and finally the decomposition of the straw powder at a lower temperature is achieved, and a wood vinegar substitute with a higher acid content is obtained, while solving the problems of high energy consumption and complex process of the traditional method. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0031] Figure 1 A process flow chart of the preparation method of the wood vinegar substitute provided by the present invention;
[0032] Figure 2 The X-ray diffraction patterns and crystallinity indexes of the cotton straw powder in step (1) of Example 1, the cotton straw powder pretreated with hydrochloric acid in step (1) of Example 1, and the cotton straw powder pretreated with potassium hydroxide in step (1) of Comparative Example 2;
[0033] Figure 3 It is the pH trend diagram of the hydrothermal reaction temperature (Y-axis offset stacking diagram, the same line represents the relative high and low pH, and the vertical coordinates between different lines do not represent the relative high and low pH, the same below);
[0034] Figure 4 It is the pH trend diagram of hydrothermal reaction time;
[0035] Figure 5 pH trend graph of the injected amount of hydrogen peroxide solution;
[0036] Figure 6 The pH value bar graph of the wood vinegar substitute prepared in Example 2, Comparative Example 3 and Comparative Example 4;
[0037] Figure 7 Component content diagram of wood vinegar substitute prepared in Example 2, Comparative Example 3 and Comparative Example 4;
[0038] Figure 8 It is the yield diagram of the wood vinegar substitute in Example 2, Comparative Example 3 and Comparative Example 4. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0041] The room temperature in the embodiments of the present invention refers to "25±2°C".
[0042] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0043] Example 1 and Comparative Examples 1-2
[0044] (1) crushing cotton straw and passing it through a 60-mesh sieve to obtain cotton straw powder; mixing the cotton straw powder with a 2wt% hydrochloric acid solution and a 2wt% potassium hydroxide solution at a solid-liquid ratio of 1:10, stirring the cotton straw powder in a 30°C water bath at a rate of 800 r / min for 3 hours to pretreat the cotton straw powder, then washing with deionized water, filtering, repeating the above washing and filtering steps until the filtrate reaches neutrality, and drying at 80°C for 24 hours to obtain hydrochloric acid pretreated cotton straw powder and potassium hydroxide pretreated cotton straw powder, respectively;
[0045] (2) 2 g of the cotton straw powder (Comparative Example 1), the cotton straw powder pretreated with hydrochloric acid (Example 1), and the cotton straw powder pretreated with potassium hydroxide (Comparative Example 2) in step (1) were respectively added to parallel reactors, and a 30% mass concentration of hydrogen peroxide aqueous solution was injected at the same time, and then the mixture was supplemented with deionized water to 20 mL, the reactor was sealed and nitrogen was passed through for 10 minutes to exhaust the air in the reactor, and a hydrothermal reaction was performed. After the hydrothermal reaction was completed, the solid and liquid phases were separated, and the obtained liquid phase was repeatedly frozen and thawed 10 times in liquid nitrogen and at room temperature, and the flocs were filtered to obtain a wood vinegar substitute;
[0046] The injection amount of the hydrogen peroxide aqueous solution, the temperature and time of the hydrothermal reaction are shown in Table 2.
[0047] Figure 2 The X-ray diffraction patterns and crystallinity indexes of the cotton straw powder in step (1) of Example 1, the cotton straw powder pretreated with hydrochloric acid in step (1) of Example 1, and the cotton straw powder pretreated with potassium hydroxide in step (1) of Comparative Example 2, wherein "no pretreatment" refers to the cotton straw powder in step (1) of Example 1, "HCl pretreatment" refers to the cotton straw powder pretreated with hydrochloric acid in step (1) of Example 1, and "KOH pretreatment" refers to the cotton straw powder pretreated with potassium hydroxide in step (1) of Comparative Example 2. Figure 2 It can be seen that the crystallinity index of the unpretreated cotton straw powder is 40.12%, the crystallinity index of the potassium hydroxide pretreated cotton straw powder obtained by pretreatment with potassium hydroxide solution in Comparative Example 2 is 43.37%, and the crystallinity index of the hydrochloric acid pretreated cotton straw powder obtained by pretreatment with hydrochloric acid solution in Example 1 is reduced to 19.01%, indicating that pretreatment of straw powder with hydrochloric acid can reduce the crystallinity of straw powder, while potassium hydroxide can increase the crystallinity of straw powder.
[0048] Taking pH as the response value, a four-factor three-level orthogonal experiment was carried out. The four-factor three-level distribution is shown in Table 1, and the four-factor three-level orthogonal table is shown in Table 2.
[0049] Table 1 Distribution of four factors at three levels
[0050]
[0051] Note: The number of factors can be less than the orthogonal array, and the blank columns are used for error analysis.
[0052] Table 2 Four factors and three levels orthogonal table
[0053] frequency A B C D 1 1 1 1 1 2 1 2 2 2 3 1 3 3 3 4 2 1 2 3 5 2 2 3 1 6 2 3 1 2 7 3 1 3 2 8 3 2 1 3 9 3 3 2 1
[0054] The pH of the wood vinegar substitutes obtained by the orthogonal experiments of Example 1 and Comparative Examples 1-2 was measured, and then the pH measurement results were analyzed by range analysis. The results are shown in Tables 3-6.
[0055] Table 3 Range analysis results of Example 1
[0056]
[0057]
[0058] Table 4 Range analysis results of comparative example 1
[0059]
[0060]
[0061] Table 5 Range analysis results of comparative example 2
[0062]
[0063] According to the K value of the range analysis in Tables 3 to 5, the pH trend chart of each factor is drawn, see Figures 3 to 5 .
[0064] Figure 3 is the pH trend diagram of hydrothermal reaction temperature, Figure 4 is the pH trend diagram of hydrothermal reaction time, Figure 5 This is a pH trend chart of the injected amount of hydrogen peroxide solution. Figure 3 to Figure 5 In the figure, the same line represents the relative high and low pH, and the vertical coordinates between different lines do not represent the relative high and low pH. Raw represents cotton straw powder without pretreatment. Figures 3 to 5 It can be analyzed that the optimal reaction conditions are a hydrothermal reaction temperature of 180°C, a hydrothermal reaction time of 90 min, and an injection volume of 5 mL of aqueous hydrogen peroxide solution.
[0065] Example 2
[0066] 2 g of the hydrochloric acid pretreated cotton straw powder obtained in step (1) of Example 1 was added to a parallel reactor, and 5 mL of a 30% mass concentration of hydrogen peroxide aqueous solution was injected at the same time, and then supplemented with deionized water to 20 mL (that is, the amount ratio of hydrochloric acid pretreated cotton straw powder, oxidant aqueous solution and water was 2 g: 5 mL: 15 mL), the reactor was sealed and nitrogen was passed for 10 min to exhaust the air in the reactor, and the reaction was carried out at 180° C. for 90 min. After the reaction was completed, the solid and liquid phases were separated, and the obtained liquid phase was repeatedly frozen and thawed 10 times in liquid nitrogen and at room temperature, and the flocs were filtered to obtain a wood vinegar substitute.
[0067] Comparative Example 3
[0068] 2 g of potassium hydroxide pretreated cotton straw powder obtained in step (1) of comparative example 2 was added to a parallel reactor, and 5 mL of a 30% mass concentration of hydrogen peroxide aqueous solution was injected at the same time, and then supplemented to 20 mL with deionized water (i.e., the amount ratio of potassium hydroxide pretreated cotton straw powder, oxidant aqueous solution and water was 2 g: 5 mL: 15 mL), the reactor was sealed and nitrogen was passed for 10 min to exhaust the air in the reactor, and the reaction was carried out at 180° C. for 90 min. After the reaction was completed, the solid and liquid phases were separated, and the obtained liquid phase was repeatedly frozen and thawed 10 times in liquid nitrogen and at room temperature, and the flocs were filtered to obtain a wood vinegar substitute.
[0069] Comparative Example 4
[0070] 2 g of the cotton straw powder in step (1) of Example 1 was added to a parallel reactor, and 5 mL of a 30% mass concentration of hydrogen peroxide aqueous solution was injected at the same time, and then supplemented with deionized water to 20 mL (i.e., the amount ratio of cotton straw powder, oxidant aqueous solution and water was 2 g: 5 mL: 15 mL), the reactor was sealed and nitrogen was passed for 10 min to exhaust the air in the reactor, and the reaction was carried out at 180° C. for 90 min. After the reaction was completed, the solid and liquid phases were separated, and the obtained liquid phase was repeatedly frozen and thawed 10 times in liquid nitrogen and at room temperature, and the flocs were filtered to obtain a wood vinegar substitute.
[0071] Figure 6 The pH value bar graph of the wood vinegar substitute prepared in Example 2, Comparative Example 3 and Comparative Example 4. Figure 6 It can be seen that the pH of the wood vinegar substitute made directly from cotton straw powder without pretreatment is 2.90, the pH of the wood vinegar substitute made from cotton straw powder pretreated with hydrochloric acid is 2.26, and the pH of the wood vinegar substitute made from cotton straw powder pretreated with potassium hydroxide is 3.14. It can be seen that pretreatment of straw powder with hydrochloric acid is beneficial to increase the content of target substances such as organic acids in the product.
[0072] The components of the wood vinegar substitute prepared in Example 2, Comparative Example 3 and Comparative Example 4 were analyzed by gas chromatography-mass spectrometry (GC-MS). 30 mL of the sample to be tested was added with 5 mL of anhydrous ether for extraction 5 times. The ether was evaporated under reduced pressure at room temperature to obtain a concentrated sample to be tested. Then, gas chromatography-mass spectrometry analysis was performed. The chromatographic column was DB-WAX (30.0 m×250 μm, 0.25 μm). The initial temperature was 60° C. and maintained for 2 min. Then, it was increased to 240° C. at a rate of 10° C. / min and maintained for 10 min. The carrier gas was helium, the carrier gas flow rate was 1.0 mL / min, the split ratio was 20:1, the mass spectrometry conditions were EI source, the electron energy was 70 eV, the scanning mass range was 35 to 550 amu, and the detection results were shown in FIG. Figure 7 .
[0073] Figure 7The component contents of the wood vinegar substitutes prepared in Example 2, Comparative Example 3 and Comparative Example 4 are shown in FIG. Figure 7 It can be seen that the acid content in the wood vinegar substitute prepared in Example 2 is 41.85%, the acid content in the wood vinegar substitute prepared in Comparative Example 3 is 37.89%, and the acid content in the wood vinegar substitute prepared in Comparative Example 4 is 32.87%.
[0074] Figure 8 Graph showing the yield of wood vinegar substitutes in Example 2, Comparative Example 3 and Comparative Example 4. Figure 8 It can be seen that the yield of the wood vinegar substitute in Example 2 is 84.82%, the yield of the wood vinegar substitute in Comparative Example 3 is 80.36%, and the yield of the wood vinegar substitute in Comparative Example 4 is 86.15%.
[0075] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a wood vinegar substitute, characterized in that: The following steps are involved: The straw powder is pretreated with hydrochloric acid to obtain pretreated straw powder; the pretreated straw powder, an oxidant aqueous solution and water are mixed and then subjected to a hydrothermal reaction, the solid and liquid phases are separated, and the obtained liquid phase is repeatedly frozen and thawed to obtain the wood vinegar substitute.
2. The method for preparing a wood vinegar substitute according to claim 1, characterized in that: The solid-to-liquid ratio of the straw powder to the hydrochloric acid is 1:
10.
3. The method for preparing the wood vinegar substitute according to claim 1 or 2, characterized in that: The straw powder includes cotton straw powder.
4. The method for preparing a wood vinegar substitute according to claim 1 or 2, characterized in that: The concentration of the hydrochloric acid is 2 wt %.
5. The method for preparing the wood vinegar substitute according to claim 1, characterized in that: The pretreatment temperature is 30° C. and the pretreatment time is 3 h.
6. The method for preparing a wood vinegar substitute according to claim 1, characterized in that: The dosage ratio of the pretreated straw powder, the oxidant aqueous solution and water is 2g:5mL:15mL.
7. The method for preparing a wood vinegar substitute according to claim 1, characterized in that: The mass concentration of the oxidant aqueous solution is 30%.
8. The method for preparing a wood vinegar substitute according to claim 1, characterized in that: The oxidant in the aqueous oxidant solution includes hydrogen peroxide.
9. The method for preparing a wood vinegar substitute according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 180° C., the time is 90 min, and the atmosphere is nitrogen.
10. The method for preparing a wood vinegar substitute according to claim 1, characterized in that: The repeated freezing and thawing is: repeated freezing and thawing 10 times in liquid nitrogen and at room temperature.
Citation Information
Patent Citations
Method for directly preparing wood vinegar through hydrothermal biomass
CN106753501A